Sentiment and Toxicity in Netizens’ Comments on Tempodotco’s ‘Alus Politik’ Leaked Video Regarding Prabowo’s Dismissal of a Minister from the Red and White Cabinet - Dien Zulfikar Hidayat; Muliadi Mau; Alem Febri Sonni; Wahyuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2026)
This paper analyses netizens’ reactions to a Tempodotco YouTube video entitled “The Reasons Prabowo Sacked Several Ministers in the Red and White Cabinet” as part of the Bocor Alus Politik program. The research focuses on sentiment analysis, toxicity, polarity distribution, and the dynamics of daily comment interactions. Data were collected using Communalytic.org from the video’s comments section, with an initial total of 2,497 comments during the observation period from 13 September to 12 October 2025. Following data cleaning and screening, the comments were processed based on language compatibility and the requirements of the analytical models. Sentiment analysis was conducted using VADER and TextBlob, whilst toxicity analysis utilized the Perspective API/Civility Analyzer. The research results indicate a predominance of neutral sentiment across all analyzed language subsets, namely 65.17% for VADER English, 89.47% for VADER Portuguese, 83.15% for TextBlob English, 100% for TextBlob French, and 98.25% for TextBlob German. Toxicity analysis of the 89 eligible comments revealed a low average toxicity score of 0.00781, with a maximum of 0.13136. These findings show that digital political discourse on YouTube does not always lead to extreme polarisation, but can also exhibit patterns of cautious, moderate, and low-toxicity reception. This study confirms that netizens act as an active audience, interpreting political messages through support, negotiation, criticism, and digital expression within YouTube’s public sphere.